Association of PTPRT mutations with immune checkpoint inhibitors response and outcome in melanoma and non‐small cell lung cancer. (4th December 2021) - Zhang, Wenjing; Shi, Fuyan; Kong, Yujia; Li, Yuting; Sheng, Chao; Wang, Suzhen; Wang, Qinghua
Abstract: Purpose: Protein tyrosine phosphatase receptor type T (PTPRT), which is a well‐known phosphatase and mutates frequently in melanoma and non‐small cell lung cancer (NSCLC). Our research aims to elucidate its mutation association with immune checkpoint inhibitors (ICI) efficacy. Methods: We integrated whole‐exome sequencing (WES)‐ based somatic mutation profiles and clinical characteristics of 631 melanoma samples received ICI agents from eight studies and 109 NSCLC samples from two studies. For validation, 321 melanoma and 350 NSCLC immunotherapy samples with targeted next‐generation sequencing (NGS) were employed. Besides, an independent NSCLC cohort contained 240 samples was also collected for further corroboration. Distinct immune infiltration was evaluated according to the PTPRT mutational status. Results: In the WES melanoma cohort, patients with PTPRT mutations harbored a significantly elevated ICI response rate (40.5% vs. 28.6%, p  = 0.036) and a prolonged survival outcome (35.3 vs. 24.9 months, p  = 0.006). In the WES NSCLC cohort, the favorable response and immunotherapy survival were also observed in PTPRT ‐mutated patients ( p  = 0.036 and 0.019, respectively). For the validation cohorts, the associations of PTRPT mutations with better prognoses were identified in melanoma, NSCLC, and pan‐cancer patients with targeted‐NGS (all p  < 0.05). Moreover, immunology analyses showed the higher mutation burden, increased lymphocyte infiltration, decreased‐ activated‐stroma, and immune response pathways were detected in patients with PTPRT mutations. Conclusion: Our investigation indicates that PTPRT mutations may be considered as a potential indicator for assessing ICI efficacy in melanoma and NSCLC, even across multiple cancers. Further prospective validation cohorts are warranted. Abstract : Our study suggests that PTPRT mutations may serve as a strong biomarker to assess ICI efficacy in melanoma and NSCLC, even across multiple cancers.